2011
DOI: 10.1038/clpt.2011.284
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Ibuprofen for Patent Ductus Arteriosus in Extremely Preterm Infants: A Randomized Controlled Study

Abstract: Our aim was to assess the hypothesis that a high-dose regimen of ibuprofen is more effective than the standard-dose regimen in closing patent ductus arteriosus (PDA) without increasing adverse effects. Infants of gestational age <29 weeks, with respiratory distress syndrome (RDS) and echocardiographic evidence of significant PDA at 12-24 h of life, were randomized to receive a standard (10-5-5 mg/kg/day) or high-dose (20-10-10 mg/kg/day) course of ibuprofen. We studied 70 infants, 35 of whom received the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…We found a significantly better PDA responsiveness to continuous infusion after a second course (efficacy of boluses vs. continuous infusion: 64.3 vs. 83.6%; p = 0.020), possibly thanks to a more constant dose being maintained, instead of the peaks and troughs obtained using boluses. This could be demonstrated by pharmacokinetic and plasma level studies, though interindividual variability is known to be high and there is no clear link between plasma levels and PDA responsiveness to pharmacological treatment [5,10,11]. As a matter of fact, the effective plasma IBU concentrations needed to close the ductus are not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found a significantly better PDA responsiveness to continuous infusion after a second course (efficacy of boluses vs. continuous infusion: 64.3 vs. 83.6%; p = 0.020), possibly thanks to a more constant dose being maintained, instead of the peaks and troughs obtained using boluses. This could be demonstrated by pharmacokinetic and plasma level studies, though interindividual variability is known to be high and there is no clear link between plasma levels and PDA responsiveness to pharmacological treatment [5,10,11]. As a matter of fact, the effective plasma IBU concentrations needed to close the ductus are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Double doses can be used in the first 12-24 h (20/10/10 mg/kg), or the interval between administrations can be reduced (12-18 h), in order to improve PDA closure rates, but this may affect toxicity (especially renal side effects). Dani et al [11] recently demonstrated that early administration (within the first 12-24 h of life) of double doses of IBU was more effective than the standard regimen in closing HsPDA (86 vs. 63% of PDA closures), but marked interindividual variations in the drug's pharmacokinetics and pharmacodynamics [9,21] make these higher doses potentially harmful in more immature infants. The trial was underpowered for detecting differences in toxicity between standard and high doses, so further evidence is needed before it can become standard practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La indometacina y el ibuprofeno reducen la vasodilatación por inhibición de la ciclooxigena y la peroxidasa; la eficacia disminuye postnatalmente por un cambio en el sistema de regulación de los vasodilatadores. Aunque la indometacina y el ibuprofeno han demostrado ser eficaces en el cierre del conducto, los efectos a largo plazo del DAP sobre la enfermedad pulmonar crónica, enterocolitis necrotizante o la supervivencia siguen (9)(10)(11) siendo temas de estudio . Más recientemente se han estudiado los efectos del paracetamol (acetaminofeno) (12,13) y el ibuprofeno oral como opciones de tratamiento .…”
Section: Introductionunclassified